Consumption effects of job loss expectations: New evidence for the euro area - António Dias da Silva; Desislava Rusinova; Marco Weißler (European Central Bank (ECB), 2023)
Probabilistic job loss expectations elicited in the Consumer Expectations Survey have predictive power for future job loss. We find that an unexpected job loss leads to a negative consumption response, while this effect is muted for workers with ex-ante job loss expectations - consistent with the Permanent Income Hypothesis. The negative consumption response to an unexpected job loss is stronger for workers who have worse perceptions of the local labour market, are older or have lower levels of liquid wealth. This supports the notion that the persistence of the unemployment shock is an important factor of the consumption response to a job loss. At the same time, we do not find a positive consumption response of workers who unexpectedly retain their job. These heterogeneous results have important implications for the expected impact on consumption of job protection measures such as job retention schemes.
Keywords: D12; D84; J63; 330; job loss expectations; consumption; ECB Consumer Expectations Survey (CES); Permanent Income Hypothesis (PIH)